Perlindungan Awak Kapal di PT Pertamina (Persero) ditinjau dari Perjanjian Kerja Laut - Ninna Ghonia; I Gusti Ayu Ketut Rachmi Handayani; Lego Karjoko (Jurnal Discretie, 2021)
PT Pertamina (Persero) is a State-Owned Enterprise (BUMN) which is engaged in the energy sector, including oil, gas, and new and renewable energy which has a shipping business sector. Ship crews have a lot of serious occupational risks. This article aims to determine the effectiveness of the protection provided by PT Pertamina (Persero) to its ship crew in terms of the Seafarers’ Employment Agreement. Legal protection for ship crew members can be seen from the compatibility of the seafarers’ employment agreement with the applicable laws and regulations. This article uses a normative legal research method (doctrinal research), namely through the collection of primary legal materials by tracing related laws and regulations and secondary legal materials obtained by collecting relevant textbooks, scientific works, journals, and previous research. The conclusion obtained from the results of the discussion is that the seafarers’ employment agreement at PT Pertamina (Persero) has not been fully able to function optimally to provide legal protection for its ship crew members.